Windows Vista step by step - Preppernau, Joan (Microsoft Press, 2007)
The smart way to learn the latest version of Microsoft Windows--one step at a time! Work at your own pace through the easy numbered steps, practice files on CD, helpful hints, and troubleshooting help to master the fundamentals of working with Windows Vista, including how to navigate the new user interface and how to use the new search features for finding anything on your desktop. You will learn how to manage files and folders to simplify your work, easily add or remove programs, hook up printers and other devices, and set up your Internet connection, email, and instant messaging. You will also discover how to use security-enhanced features to help protect your PC, as well as how to share your computer while still helping keep personal settings and files private. You'll even learn how to enjoy all your favorite entertainment--music, pictures, and more--all in one place. With STEP BY STEP, you can take just the lessons you need or work from cover to cover. Either way, you drive the instruction--building and practicing the skills you need, just when you need them!